Hadith #3000 - Sunan Abi Dawud - ibn Abbas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ikrama عكرمة; Masraf bin 'Amr bin al-Sari مصرف بن عمرو بن السري; Sa'id bin Jubayr سعيد بن جبير الأسدي; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Sunan Abi Dawud)
Ka’ab bin Malik who was one of those whose repentance was accepted said “Ka’ab bin Al Ashraf used to satire the Prophet (ﷺ) and incited the infidels of the Quraish against him. When the Prophet (ﷺ) came to Madeena, its people were intermixed, some of them were Muslims and others polytheists aho worshipped idols and some were Jews. They used to hurt the Prophet (ﷺ) and his Companions. Then Allaah Most High commanded His Prophet to show patience and forgiveness. So Allaah revealed abou
Grade: Da'if

Hadith #3001 - Sunan Abi Dawud - Ibn Ishaq محمد بن إسحاق بن يسار‎; Masraf bin 'Amr bin al-Sari مصرف بن عمرو بن السري; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
Ibn ‘Abbas said “When the Apostle of Allaah(ﷺ) had victory over Quraish in the batte of Badr and came to Madeenah he gathered the Jews in the market of Banu Qainuqa and said “O community of Jews embrace Islam before you suffer an injury as the Quraish suffered.” They said “Muhammad, you should not deceive yourself (taking pride) that you had killed a few persons of the Quariash who were inexperienced and did not know how to fight. Had you fought with us, you would have known us. You
Grade: Da'if

Hadith #3040 - Sunan Abi Dawud - Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; ibn Abbas; Masraf bin 'Amr bin al-Sari مصرف بن عمرو بن السري; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Sunan Abi Dawud)
‘Ali said “If I survive for the Christians of Banu Taghlib I shall kill fighters and captivate children for I had written a document between them and the Prophet(ﷺ) to the effect that they would not make their children Christian. Abu Dawud said “This is rejected (munkar) tradition and it has reached me from Ahmad (bin Hanbal) that he used to reject this tradition seriously. Abu ‘Ali said “Abu Dawud did not present this (tradition) in this second reading.”
Grade: Da'if